2022
DOI: 10.1126/sciadv.abj8812
|View full text |Cite
|
Sign up to set email alerts
|

Calcineurin and huntingtin form a calcium-sensing machinery that directs neurotrophic signals to the nucleus

Abstract: When a neurotrophin binds at the presynapse, it sends survival signals all the way to the nucleus on signaling endosomes. These endosomes fuel their own journey with on-board glycolysis-but how is that journey initiated and maintained? Using microfluidic devices and mice, we find that the calcium released upon brain-derived neurotrophic factor (BDNF) binding to its receptor, tropomyosin receptor kinase B (TrkB), is sensed by calcineurin on the cytosolic face of the endosome. Calcineurin dephosphorylates huntin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 70 publications
0
17
0
Order By: Relevance
“…The anterograde transport of SVP is driven predominantly by the kinesin-3 motor KIF1A (Guedes-Dias and Holzbaur, 2019). HTT and KIF1A interactomes suggested a possible interaction between the two proteins (Shirasaki et al, 2012;Stucchi et al, 2018), but HTT has not yet been shown to interact functionally with KIF1A. We observed KIF1A in the proteome of HTT-associated vesicles (Fig.…”
Section: Htt Recruits Kif1a To Vesiclesmentioning
confidence: 69%
See 2 more Smart Citations
“…The anterograde transport of SVP is driven predominantly by the kinesin-3 motor KIF1A (Guedes-Dias and Holzbaur, 2019). HTT and KIF1A interactomes suggested a possible interaction between the two proteins (Shirasaki et al, 2012;Stucchi et al, 2018), but HTT has not yet been shown to interact functionally with KIF1A. We observed KIF1A in the proteome of HTT-associated vesicles (Fig.…”
Section: Htt Recruits Kif1a To Vesiclesmentioning
confidence: 69%
“…To investigate whether HTT and its phosphorylation affect the transport of SVP in a physiologically relevant system, we reconstituted mature corticostriatal circuits in microfluidic devices (Moutaux et al, 2018; Virlogeux et al, 2018). These devices have been used to establish HTT’s role in the transport of organelles such as BDNF-containing vesicles and signaling endosomes (Gauthier et al, 2004; Liot et al, 2013; Scaramuzzino et al, 2022; Virlogeux et al, 2018). Microfluidics consist of a presynaptic and a postsynaptic compartment containing cortical and striatal neurons, respectively, and a middle synaptic compartment that receives axons from cortical neurons and dendrites originating from striatal neurons ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ser421 phosphorylation by AKT, and dephosphorylation by calcinurin, recruits and releases kinesin, respectively, thereby determining the direction of vesicle transport (e.g. BDNF) (Colin et al, 2008; Scaramuzzino, Cuoc, Pla, Humbert, & Saudou, 2022), while phosphorylation of this site is also reported to decrease huntingtin-cleavage and fragment-toxicity (Warby et al, 2005) and to influence mitochondrial phenotypes and toxicity in HD neuronal cells (Xu et al, 2020). CDK5 phosphorylation of pSer434 was associated with decreased caspase cleavage of huntingtin (Luo, Vacher, Davies, & Rubinsztein, 2005), whereas CDK5 phosphorylation of pSer1181 and pSer1201was reported to mediate huntingtin toxicity in neuronal cultures (Anne, Saudou, & Humbert, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Despite its poor brightness, mCherry is a popular RFP for cellular sensing and imaging because of its widespread availability in a plethora of fusion constructs. 25,26 This monomeric RFP traces its lineage from the naturally occurring tetramer DsRed. 27 The consequent engineering strategies on DsRed resulted in a FP with high expression and fast chromophore maturation, low phototoxicity, and a favorable red-shift of absorption and emission spectra.…”
Section: Introductionmentioning
confidence: 99%